Research into the causes of increased vibration levels on the diesel-electric generators set at the air traffic control - Belgrade Airport - Žegarac, Nikola P. (Vojnotehnički glasnik / Military Technical Courier, 2015)
The paper presents the research into the causes of increased vibration levels on the diesel-electric generators at the Air Traffic Control-Belgrade Airport. The types of diesel generating sets are of the 175 KVA No-Break type (no interruption in electricity supply). Diesel generators serve as a backup power source (duplex system) in case of interruption in the regular electricity supply from the city grid for the systems and devices of the Air Traffic Control at Belgrade Airport. One diesel generator is in continuous operation, while the second diesel engine serves as a backup power system. The determined vibrodiagnostic methods for evaluating the technical functioning of diesel generators are an integral part of the documentation for the maintenance and overhaul of the No-Break diesel-generating set.
Keywords: diesel-generator sets; measurement and analysis of vibration; vibration levels; vibration diagnostics; vibration parameters; technical correctness of diesel generators